ANALISIS MODEL PENERIMAAN SISTEM TEKNOLOGI AKUNTANSI DISEKTOR UMKM JAYAPURA DENGAN PENDEKATAN MODEL TECHNOLOGY ACCEPTANCE MODEL (TAM) - Purbananda, Bonang Pamungkas; Falah, Syaikul; Simanjuntak, Aaron (APSSAI, 2022)
This study aims to analyze the accounting technology acceptance method using the Technology Acceptance Model or TAM with a sample of 275 MSME running information systems. The data is processed using descriptive analysis with SEM data processing. The results of the study are (1) perceived ease of use has an effect on perceived usefulness with a significant level of 0.000; (2) perceived usefulness has no effect on attitude toward using (attitude); (3) perceived ease of use has no effect on attitude toward using (attitude); (4) attitude toward using (attitude) has no effect on behavioral intention (intention); (5) perceived usefulness has a direct effect on the behavioral intention with a significant level of 0.0001; (6) behavioral intention (intention) has no effect on actual usage (real users).